2010
DOI: 10.1590/s0365-05962010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Acne e dieta: verdade ou mito?

Abstract: Numerous studies were published over the last 50 years to investigate whether diet is associated with the etiology of acne. Although older studies well known by dermatologists that refute the association between acne and diet exist, their scientific foundation is weak. New articles have recently brought to light evidence contrary to previous findings. Therefore, we would like to investigate whether diet, directly or indirectly, influences one or more of the four fundamental etiopathogenic pillars of acne: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 70 publications
(99 reference statements)
0
20
1
4
Order By: Relevance
“…2,13-20 Lack of confidence, social withdrawal, feelings of insecurity and inferiority, limited employment opportunities, difficulties at work and in interpersonal relationships, and suicidal ideation are also related to the effects of changes in individuals with acne. 2,5,6,10,16 …”
Section: Discussionmentioning
confidence: 99%
“…2,13-20 Lack of confidence, social withdrawal, feelings of insecurity and inferiority, limited employment opportunities, difficulties at work and in interpersonal relationships, and suicidal ideation are also related to the effects of changes in individuals with acne. 2,5,6,10,16 …”
Section: Discussionmentioning
confidence: 99%
“…12,18 Hyperinsulinemia plays a role in circulating concentration of IGF-1 and the growth factor binding protein similar to insulin-3 (IGFBP-3), which act directly on the proliferation of keratinocytes and apoptosis. IGF-1 seems to mediate comedogenic factors, like androgens, growth hormone and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8,9 Many authors say that the diet doesn't influence the appearance of acne and that such a statement is nothing but a myth. However, Costa et al (2010), based on various literature reviews, said the not westernized people do not suffer from acne, because their food doesn't include processed foods, such as dairy products, refined sugars and oils. Smith et al also found, in a clinical trial, in which a group was exposed to a diet with low glycemic load (GL) and a control group to a diet with high GL, that after 12 weeks, the group with low diet GL presented a significant reduction in the number of acne lesions.…”
mentioning
confidence: 99%
“…Smith et al also found, in a clinical trial, in which a group was exposed to a diet with low glycemic load (GL) and a control group to a diet with high GL, that after 12 weeks, the group with low diet GL presented a significant reduction in the number of acne lesions. 2,4,10,11 Although the diagnosis of acne is a relatively easy rule, the various forms may require a differential diagnosis.…”
mentioning
confidence: 99%